TANGGUNG JAWAB HUKUM KURATOR ATAS PENGURUSAN DAN PEMBERESAN HARTA PAILIT - herlina herlina; ilham abbas; andi Risma (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2021)
Abstract: Herlina 04020170324: Curator and Legal Responsibility for the Management and Settlement of Bankruptcy Assets. Under Dr. Ilham Abbas., S.H., M.H as the Chief Advisor and Dr.Hj.Andi Risma.S.H., M.H as the Advisor. This study aims to determine and analyze the legalresponsibility of the curator in managing and resolving bankruptcy assets and to find out and analyze the sanctions for the curator if there is an error or negligence in his responsibility. In thislegal research the writer uses a normative legal approach. In the normative legal approach, onlylibrary materials or secondary data are studied, which include primary and secondary legal materials. By conducting studies and analysis of legal protection for curators against creditors and lawsuits in the management and settlement of bankruptcy assets in terms of literature and Law No.37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The results of this study illustrate that the curator is personally responsible and the curator must pay for the losses it incurs by himself, where this responsibility can occur, for example, if the curatorembezzled bankruptcy assets and any losses incurred, as a result of negligence or due to unprofessionalism of the curator becomes the responsibility of the curator , therefore, the loss cannot be borne by the bankruptcy estate. As a suggestion It is better if the curator in managing and resolving bankruptcy assets, the curator should carry out his duties carefully and professionally. Regarding the demands that can be given to the curator, demands may be made if the curator carries out his responsibilities deviating from the provisions of laws and other regulations. Abstrak: Herlina 04020170324: Tanggung Jawab Hukum Kurator Atas Pengurusan Dan Pemberesan Harta Pailit. Di Bawah Bimbingan Dr. Ilham Abbas.,S.H.,M.H sebagai Ketua Pembimbing dan Dr.Hj.Andi Risma.S.H.,M.H sebagai Anggota Pembimbing. Penelitian inibertujuan Untuk mengetahui dan menganalisis Tanggung Jawab Hukum Kurator dalam pengurusan dan pemberesan harta pailit dan Untuk mengetahui dan menganalisis sanksi bagi kurator apabila terdapat kesalahan atau kelalaian dalam tanggung jawabnya. Dalam penelitian hukum ini penulis menggunakan pendekatan hukum normatif. Pada pendekatan hukum normatif yang diteliti hanya bahan pustaka atau data sekunder, yang mencapkup bahan hukum primer dansekunder. Dengan melakukan pengkajian dan analisis terhadap perlindungan hukum bagi kurator terhadap tuntutan hukum kreditur dalam pengurusan dan pemberesan harta pailit ditinjau dari berbagai Literatur dan Undang-Undang No.37 Tahun 2004 Tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang. Hasil Penelitian ini menggambarkan kurator bertanggung jawab secara pribadi dan kurator harus membayar sendiri kerugian yang ditimbulkannya, dimana tanggung jawab ini dapat terjadi, misalnya, jika kurator menggelapkan harta kepailitan dan segala kerugian yang timbul, sebagai akibat dari kelalaian atau karena ketidakprofesionalan kurator menjadi tanggung jawab kurator, oleh karenanya kerugian tersebut tidak bisa dibebankan pada harta pailit. Sebagai Saran Sebaiknya kurator dalam pengurusan dan pemberesan harta pailit kurator melaksanakan tugasnya dengan teliti dan profesional. Mengenai tuntutan yang dapat diberikan kepada kurator, tuntutan bisa saja diberikan jika kurator melaksanakan tanggung jawabnya melenceng dari ketentuan Undang-undang dan peraturan lain.